CLASSIFICATION OF TAFSIR MAUDHU'I MAHMUD SYALTUT - Amir, Asrul; Arianto, Rudy; Misbahuddin, Adriyan (Hunafa: Jurnal Studia Islamika, 2023)
Various methods of exegesis have been born which in essence are attempts to reveal the meanings of the Qur'an. The most popular maudhu'i (thematic) interpretation method for this matter. The majority of scholars are of the opinion that maudhu'i interpretation is revealing the meanings of the Qur'an and explaining its more general meanings, and explaining difficult-to-understand pronunciations. This article uses the library research method (Library Research) which requires qualitative data. This research is based on the contents of books, journals, and other library sources. This method is very commonly used so it is easy to understand. The objectives to be achieved from this article are to find out the biography of Mahmud Syltut, to find out the identity of the printed book to the method used by Mahmud Shaltut in writing his commentary. So that we can find the meaning of the word Maudhu'i according to Mahmud Syaltut "That the maudhu'i method, in addition to other methods, is a very good method, especially for materials published to the public, with the aim of giving them instructions about various kinds of guidance. contained in the Koran.